Students' Difficulties In Learning Arabic At Man 1 Medan - Arridho Prasetiyo Pradana Putra; Ahmad Taufiq Lubis; Alwi Asnawi Nasution; Sahkholid Nasution (Sean Institute, 2025)
This articles explain the Factors of Student Difficulty in Learning Arabic at MAN 1 Medan. This research is very important to carry out to find out the various factors that become obstacles for MAN 1 Medan students in learning Arabic and find solutions . This study uses a qualitative method . Research participants were students of MAN 1 Medan. Data collection methods and techniques were in the form of questionnaire distributed to students at MAN 1 Medan and interviews conducted with several students and teachers teaching Arabic subjects . The findings from this research show that students ' difficulties in learning Arabic is influenced by five factors consisting of internal and external factors, namely, first , the students ' lack of memorizing Arabic vocabulary . Second , the lack of student interest in learning Arabic . Third , students come from various different elementary school educational backgrounds . Fourth , the teacher factor , which can be seen from teaching methods that is less attractive and the abilities to manage the class that is not optimal. Fifth , environmental factors , for example the use of regional languages at home which is more dominant than Arabic.